Bioassays Application for Mutagenicity and Cytotoxicity Evaluation of Medicinal Plant having Considerable Antioxidant Potential - Ali, Abid; Rahman, Khalil-ur-; Shahid, Muhammad; Arshad, Muhammad (Asian Journal of Chemistry, 2015)
The main focus of the present study was to explore antioxidant and toxicological profile of Silybum marianum. The antioxidant activity of methanolic extract of S. marianum was assayed using the diphenyl-picrylhydrazine (DPPH) radical scavenging and H2O2 induced DNA protection assay. The cytotoxicity of the plant extract was evaluated by hemolytic, brine shrimp lethality and mutagenic activity by Ames test. The percentage inhibition for DPPH ranged from 51 to 76 at concentration 10 and 100 mg/mL. The methanolic extract exhibited DNA protection on concentration dependent manner and complete protective effect was noted at concentration 10 μL/mL. Toxicological results showed that S. marianum was potent against hemolytic, brine shrimps and non-mutagenic against standard mutagens that indicated the presence of some bioactive components in the plant and possessed antioxidant activity that protects DNA against H2O2 induced oxidative damage. Thus, the results showed that S. marianum exhibited significant bioactive components with least side effects. The present investigation will provide better scientific basis for future pharmacological evaluation due to its novel nature. In vivo studies and identification of novel source of pure bioactive compounds will be performed in future studies.